2017
DOI: 10.1515/raon-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of the effectiveness of stereotactic ablative radiotherapy versus conventional fractionated radiotherapy for clinical stage I non-small cell lung cancer patients

Abstract: BackgroundStereotactic ablative radiotherapy (SABR) is a promising option for non-operated early-stage non-small cell lung cancer (NSCLC) compared to conventional fractionated radiotherapy (CFRT). However, results from conclusive randomized controlled trials are not yet available. The aim of our study was to explore the effectiveness of SABR vs. CFRT for non-operated early-stage NSCLC.Patients and methodsWe used a comprehensive population-based database to identify clinical stage I non-operated NSCLC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“… 20 Another study using a population‐based database of Taiwan found that nonoperated NSCLC receiving SABR had 5‐year OS of only 31%. 21 The 5‐year OS of 58.3% noted in this study is between the previous two studies and may reveal the current situation of a medical center in Taiwan. The local recurrence rate of 7.5% at 5‐years in the current study is comparable to the 6.3% noted in the revised STARS trial.…”
Section: Discussionsupporting
confidence: 65%
“… 20 Another study using a population‐based database of Taiwan found that nonoperated NSCLC receiving SABR had 5‐year OS of only 31%. 21 The 5‐year OS of 58.3% noted in this study is between the previous two studies and may reveal the current situation of a medical center in Taiwan. The local recurrence rate of 7.5% at 5‐years in the current study is comparable to the 6.3% noted in the revised STARS trial.…”
Section: Discussionsupporting
confidence: 65%
“…Six articles compared all-grade AEs [ 9 , 11 , 13 , 20 , 22 , 23 ] (Supplementary Digital Content, Table 4). The 10 most commonly reported AEs in all grades were pneumonitis, dyspnea, cough, fibrosis, acute kidney disease, radiation pneumonitis, skin reactions, fatigue, and chest wall pain (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five articles referred to grade 3–5 AEs, [ 9 , 11 , 13 , 20 , 23 ] in which SBRT was associated with no obvious difference (RR: 0.68 [0.30-1.53], P = .35) when compared with CRT (heterogeneity: P = .08, I 2 = 52%, Fig. 2 D) (Supplementary Digital Content, Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The date of diagnosis in the TCR was defined as the index date, and OS was calculated from the date of diagnosis to the date of death, or 31 December 2017 (the censoring date of the death registry). The related covariates were collected based on the literature, 5,8 as well as based on our experiences in clinical care 9 and TCR studies, [10][11][12] to adjust for potential nonrandomized treatment selection (see below).…”
Section: Study Population and Designmentioning
confidence: 99%